The role of the oral hygienist in the public sector in KwaZulu-Natal and Gauteng Province - Govender, Urvashnee (My University, 2010)
Introduction: There are high levels of dental caries, gingival and periodontal diseases and a lack of oral health awareness in the wider South African population. Thus every district’s oral health strategy must include disease prevention and health promotion approach. Oral hygienists are the main drivers of these services in the public sector. Aim: To determine the activities of oral hygienists in the public sector in Gauteng and KwaZulu – Natal provinces. Objectives: 1) To obtain the demographic profile of oral hygienists employed in Gauteng and KwaZulu -Natal provinces. 2) To determine their current duties, tasks and responsibilities. 3) To identify factors that may hinder the provision of services. Methods: This was a cross sectional descriptive study and data was collected by means of a self administered questionnaire that was hand delivered to all oral hygienists employed in Gauteng and in KwaZulu - Natal provinces in 2005. Results: Thirty two oral hygienists (78%) responded to the questionnaire, 94% of whom were female with an average age of 37 years. Twenty three (72%) were Black, 6 (19%) White, 2 (6%) Indian and 1 (3%) Coloured, with an average iv working experience of 10 years. Almost half (47%) were employed as chief, 16% as senior and 37% as junior oral hygienist. Almost all (94%) complained of poor salaries and 78% said that there were no opportunities for promotion. Oral hygienists performed both clinic-based and community-based services. The majority (95%) of the community-based services was preventive; the most common preventive services being rendered to the community was oral health education (84%), brushing programs (75%) and examination, charting and screening (69%). Seventy seven percent (77%) of clinic-based services included preventive procedures the most common being scaling and polishing or root planing (88%), examination and charting (84%) and oral hygiene instructions (75%). The majority of oral hygienists (94%) worked in the public sector to provide a service to the community. Seventy six percent (76%) had experiences that hindered the provision of services. Almost all (97%) wanted to study further, the main area of interest being the dental field. Conclusion: It is evident that the duties, tasks and responsibilities of oral hygienists in both KZN and GP include activities associated predominantly with the prevention and control of oral diseases and oral health promotion. In South Africa, a decline in oral diseases (dental caries and periodontal diseases) can be achieved by enhancing the use of oral hygienists in the public sector.
MPH, Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: Gauteng; KwaZulu-Natal; role of oral hygienist